1997
DOI: 10.1021/es970451s
|View full text |Cite
|
Sign up to set email alerts
|

A Computationally-Based Hazard Identification Algorithm That Incorporates Ligand Flexibility. 1. Identification of Potential Androgen Receptor Ligands

Abstract: To advance techniques for screening large data sets of diverse structures for toxicologically active compounds, an algorithm was developed that is not dependent upon a predetermined and specified toxicophore or an alignment of conformers to a lead compound. Instead, the approach provides the means to identify and quantify specific global and local stereoelectronic characteristics associated with active compounds through a comparison of energeticallyreasonable conformer distributions for specific descriptors. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
47
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 63 publications
(48 citation statements)
references
References 40 publications
1
47
0
Order By: Relevance
“…The analysis was focused on the distance between nucleophilic sites, the oxygen atoms of 3-carbonyl and a 17-OH group. Results from previous SAR investigations have indicated that the 3-carbonyl atom in the A-ring and a 17-OH group in the D-ring, along with a steroid hydrophobic backbone, significantly contribute to the high affinity binding of steroids to the AR [30]. In this respect the probabilistic conformer distributions of most active chemicals was analysed.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The analysis was focused on the distance between nucleophilic sites, the oxygen atoms of 3-carbonyl and a 17-OH group. Results from previous SAR investigations have indicated that the 3-carbonyl atom in the A-ring and a 17-OH group in the D-ring, along with a steroid hydrophobic backbone, significantly contribute to the high affinity binding of steroids to the AR [30]. In this respect the probabilistic conformer distributions of most active chemicals was analysed.…”
Section: Resultsmentioning
confidence: 99%
“…Based on thermodynamic and kinetic considerations [30], it has been shown that at macromolecular binding sites conformational states can be populated that are substantially different from those of isolated, lowest-energy or crystal-phase states. Conformers of an individual chemical that have free energy within a range of approximately 20 kcal mol À1 from the lowest energy structure (usually accepted as a threshold) often exhibited significant variation in potentially relevant electronic descriptors.…”
Section: Chemical Inventory For Selecting Chemicals For Strategic Tesmentioning
confidence: 99%
“…The COREPA is a probabilistic classification scheme identifying criteria which will classify an unknown object into predefined classes using a training set composed of objects from multiple classes [45,46]. The COREPA formalism uses a Bayesian probabilistic method to identify common structural characteristics among chemicals that elicit similar biological activity.…”
Section: Methodsmentioning
confidence: 99%
“…Thus, an expert system (OASIS) was employed to screen the chemicals from the HPV list for phototoxicity and endocrine disruption ability. Of all HPV organics, 3.3% were found to meet the electronic and bioaccumulation requirements for phototoxicity (Mekenyan et al, 1994), whereas about 1.5% were found to be similar to the electronic pattern enhancing binding affinity to androgen receptors (Mekenyan et al, 1997). E Dangerous to the aquatic environment E Acute toxicity E Dermal irritation/corrosion E Eye irritation/corrosion E Sensitization E Reproductive toxicity E Germ-cell mutagenicity E Carcinogenicity E Organ toxicity after repeated exposure E End points not currently covered by existing classification systems (e.g., neurotoxicity, immunotoxicity, terrestrial toxicity)…”
Section: New Developmentsmentioning
confidence: 99%